MONITORING SOIL EROSION BY RASTER IMAGES: FROM AERIAL PHOTOGRAPHS TO DRONE TAKEN PICTURES - Pérez, Eugenia; García, Pilar (European Journal of Geography, 2017)
With the aim of understanding the evolution of soil erosion in an ecologically degraded area in southeast Madrid (Spain), an analysis is conducted on a series of aerial photographs, multitemporal satellite images and high resolution photographs taken from a drone. This natural space has been selected as a pilot project for monitoring soil erosion in recently urbanized areas built on clastic sediments and soils. This characteristic landscape is mainly covered by gullies and is subject to high surface run-off. The evolution of soil erosion varies significantly depending on anthropic influences and vegetation cover. Soils are highly pervious and classified as regosols and arenosols, mixed with luvisols and cambisols where Mediterranean vegetation is present. Recent urbanization has increased the erosion of sandy materials. A better understanding of the soil loss processes will be useful in land use and urban planning.